2020
DOI: 10.3390/su12125118
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Aspect of Human Resource Management as a Determinant of the Potential of Polish Hospitals to Manage Medical Professionals in Healthcare 4.0

Abstract: Industry 4.0 solutions have penetrated the healthcare sector, thus creating challenges that healthcare entities should meet. For this, a proper relationship between human resource management (HRM) within healthcare entities and Healthcare 4.0 is needed. In addition, organizations mainly focus on HRM practices, yet organizational issues are overlooked. In this context, the aim of the article was to analyze and evaluate the involvement and roles of key HRM actors, such as line managers and human resource (HR) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
(36 reference statements)
0
25
0
2
Order By: Relevance
“…Previous researches on human resource in the healthcare sector have shown that the demand for medical personnel is rapid growth [ 12 ] and the capacity of human resource managers [ 13 ], the remuneration, career development, and succession plan [ 14 ] are important factors in the development of human resources in health. However, these research or talent acquisition measures were based solely on the perspective of local government health departments or medical institutions, focused on individual health care workers and with less research on PHCIs.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Previous researches on human resource in the healthcare sector have shown that the demand for medical personnel is rapid growth [ 12 ] and the capacity of human resource managers [ 13 ], the remuneration, career development, and succession plan [ 14 ] are important factors in the development of human resources in health. However, these research or talent acquisition measures were based solely on the perspective of local government health departments or medical institutions, focused on individual health care workers and with less research on PHCIs.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…HR leaders need to redefine their mandate and gear up for the new world of work which calls for smart HRM practices or HR 4.0 in organizations. Many recent studies also highlight that diverse technological advancement in Industry 4.0 will require an adapted and well-equipped strategic HRM, aligned with organizational goals and policies (Buchelt et al, 2020; Dhanpat et al, 2020; Liboni et al, 2019). Many authors believe that HR leaders, key technical personnel, and executives of the HR department must be updated, competent, trained, meticulous, skilled, and efficient to perform HR functions such as hiring, training, compensation, performance appraisal, safety, wellness, benefits, training of employees, motivation, retention, and change management while navigating Industry 4.0 (Buchelt et al, 2020; Kulyk and Parmova, 2017; Llinas and Abad, 2019; Shaw and Varghese, 2018; Sony and Naik, 2020; Strohmeier, 2018).…”
Section: Findings and Analysismentioning
confidence: 99%
“…Studies by Buchelt et al (2020) and Dhanpat et al (2020) reveal that to mitigate challenges, HR professionals will need to assume the roles of strategic business leaders with competencies such as innovator, strategic partner, change agent, and people enablement. Cresnar and Nedelko (2020) mention that the personal values of HR professionals and employees will be significant in shaping the organizational environment for Industry 4.0.…”
Section: Findings and Analysismentioning
confidence: 99%
“…Healthcare 4.0 is a collective term for concepts derived from Industry 4.0 like data-driven digital health technologies, such as smart health, mobile health, wireless health, e-health, online health, medical IT, telemedicine, digital medicine, health informatics, pervasive health, and the health information system (Buchelt et al, 2020). In-depth analysis of Healthcare 4.0 implications reveals the fact that the effects of the revolution are progressing in two different ways:…”
Section: Related Workmentioning
confidence: 99%